STRATEGI PEMASARAN TRANSAKSI DIGITAL BANK CENTRAL ASIA (BCA) SEBAGAI SARANA MENINGKATKAN JUMLAH NASABAH - Adityo Seto Nordiantoro (2021)
Develop digital technology greatly affects people's habits in carrying out activities, especially in transactions. Advances in digital technology have made the banking industry in Indonesia more competitive in issuing innovations related to digital banking. Along with the development of information and communication technology, financial services industry such as banking today have various variations in attracting customers, which causes the level of competition to be higher. During the pandemic, its recorded that digital banking transactions experienced a very rapid increase. The banking industry in Indonesia is increasingly competing to market its digital products during the pandemic, including Bank Central Asia (BCA). This study intends to find the effect of Bank Central Asia's (BCA) digital transaction marketing strategy on the number of customers. This analysis uses qualitative analysis methods. The source used as material for analysis is derived from the annual financial report of Bank Central Asia (BCA) with the aim of describing and summarizing various conditions related to BCA digital transactions that have occurred in recent years. The results of this study also show that the digital transaction marketing strategy of Bank Central Asia (BCA) has an impact on the growth in the number of customers every year.